2014
DOI: 10.1007/s10867-014-9345-0
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Modulating DNA configuration by interfacial traction: an elastic rod model to characterize DNA folding and unfolding”

Abstract: In this comment, we point out that the tractions induced by interfacial energy, which are referred to as the tractions on the central axis curve of the DNA elastic rod presented by Huang (J. Biol. Phys. 37(1), 79-90, 2011), are incorrect. The correct tractions are provided in this literature. Further, with the use of the correct tractions, we present new numerical results, which for the values given by Zaixing Huang do not give rise to the physical behavior observed for DNA by the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…where f i refers to the interfacial traction, which characterizes the effects of the intracellular solution on the rod (Xiao et al, 2014;Wang et al, 2014).…”
Section: Kirchhoff's Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…where f i refers to the interfacial traction, which characterizes the effects of the intracellular solution on the rod (Xiao et al, 2014;Wang et al, 2014).…”
Section: Kirchhoff's Equationsmentioning
confidence: 99%
“…The interaction between the DNA elastic rod and the molecules of the solution plays a significant role in the reconfiguration of the DNA segments (Benham and Mielke, 2005). Several studies (Huang, 2011;Xiao et al, 2014;Wang et al, 2014) have shown that microequilibrium configurations of DNA chains are affected by the interaction of the DNA molecule with positive ions in a salt solution. Huang (2011) modeled the interaction using distributed traction, which is caused due to interfacial energy, in a Kirchhoff model, and characterized the folding and unfolding of DNA chains using a numerical simulation of the elastic model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In salt solution, the geometrical configuration of a DNA chain is determined by the interaction between DNA chain and solution molecules. Huang [9] modeled the interaction by the interfacial traction in an elastic rod model, which characterized DNA folding and unfolding, and Wang et al [10] corrected the incorrect tractions induced by the interfacial energy. Xiao et al [11] used the elastic rod model to evaluate the effects of ionic concentration on the equilibrium configuration.…”
mentioning
confidence: 99%